Porous anion exchange membranes fabricated by phase inversion and in‐situ modification for acid recovery. Issue 21 (10th October 2022) - You, Xinqiang; Chen, Jiaqi; Teng, Lin; Lin, Jiuyang; Lin, Xiaocheng
Abstract: Diffusion dialysis (DD) for acid recovery is significantly restricted by the poor acid dialysis coefficient ( U H + ) of anion exchange membranes (AEMs). To overcome such problem, porous AEMs with extremely high free space volume have been fabricated herein based on porous membrane substrate, drawing inspiration from the dissolution‐diffusion concept. Specifically, chloromethylated polyethersulfone (CMPES) has been used as the starting material to create the porous substrate via non‐solvent phase inversion, then in‐situ crosslinked and quaternized using ethylenediamine (EDA) and N‐methylimidazole (NMI), respectively. In this study, the degrees of modification of EDA and NMI are controlled to adjust the microstructure and DD performance of the produced porous AEMs. The ideal AEM's U H + and acid/salt separation factor ( S ) are 4.3 and 2.6 times greater, respectively, than those of the commercial DF‐120 membrane at the same condition. Additionally, it shows strong organic solvent resistance and thermal stability, and therefore demonstrate the potential for widespread use. Abstract :